The Consequence of Capital Expense to the Economic Development of South Sulawesi Province - Andi Putri; Muh. Arif (www.amertainstitute.com, 2025)
The purpose of this study is to determine and review consequence of the capital expense in the form of: capital expense for tools and instruments, capital expense for buildings and structures, avenue capital expense, dams and waterways, and further fixed asset capital expense on economic development Province of South Sulawesi. The analysis method uses a descriptive approach that aims to describe the development of capital expense and economic development Province of South Sulawesi from period to period, and the inferential approach with regression analysis, which is an analysis to find out of capital effect expense development of economic. Analyze results found that the economic development of South Sulawesi Province fluctuated relatively from year to year, but remained in a stable condition, as well as capital expense which tended to fluctuate. Regression results show that capital expense for tools and instruments and capital expense for buildings and structures have a negative impact on economic development. But capital expenses on avenues, dams, waterways, and other fixed asset capital expenses get a positive also important impact on the development of the economy.